Communicative Inequality of Cross-Language Correspondences in Translation - I. A. Lekomtseva; I. A. Nagovitsyna (Научный диалог)
The questions connected with the definition of communicative inequality of interlingual correspondences in translation are considered. It is noted that the correspondence between the units of the original text and the translation text can be represented by stable cross-language facts, which in turn in the conditions of this context are either communicative equivalent or communicative unequal. It is pointed out that the reason is the discrepancy between the language unit in the language system and its implementation in speech, that is, when translating it is important to determine the proper inter-language correspondences, and the correspondences between their uses in speech. In this regard, the authors use the notion of idiomaticity, which after N. K. Ryabtseva is defined as the typicity, stability of the use (combination) of linguistic units in speech. It is proved that when translating, the cross-language correspondences between the units of the source text and the translated text are found out at the level of the dictionary meanings of the lexemes with the preservation of grammatical forms and structures, but nevertheless, these correspondences are communicative uneven and inadequate from the point of view of their use in speech, and this determines the relevance of the study.